Pengaruh Kompensasi terhadap Kepuasan Kerja dengan Motivasi Kerja Sebagai Variabel Intervening : Studi Kasus Pada PT. Tiga Mutiara Nusantara Bagian Moulding di Kec. Dolok Merawan - Saragih, Ranti Dwi Putri; Mayastika, Eka; Tampubolon, Lasmaria (STIE Bina Karya, 2024)
This study aims to determine the effect of compensation on job satisfaction with motivation as an intervening variable. This type of research is quantitative research. The sample in this study is employees of PT. Tiga Mutiara Nusantara Molding Section in Dolok Merawan District totaling 53 people. The results of the study show that hypothesis 1 is accepted, namely Compensation (X) affects the Work Motivation variable (Z), the second hypothesis is accepted, namely Compensation (X) affects the Job Satisfaction variable (Y) and the third hypothesis is accepted, namely Work Motivation (Z) affects the Job Satisfaction variable (Y). The indirect influence through the Work Motivation variable (Z) is smaller than the direct influence on the Job Satisfaction variable (Y) which means that Work Motivation cannot act as an intervening variable.